2022
DOI: 10.1108/imds-12-2021-0772
|View full text |Cite
|
Sign up to set email alerts
|

National Innovation Demonstration Zone policy and city innovation capability – a quasi-natural experimental analysis

Abstract: PurposeThis paper aims to understand the relationship between the National Innovation Demonstration Zone policy and city innovation capability and the underlying mechanisms.Design/methodology/approach This paper collects panel data of 283 Chinese cities from 2006 to 2018 for the quasi-natural experiment of National Independent Demonstration Zone (NIDZ) policy. It applies the difference-in-difference (DID) method to study the impact of NIDZ policy on city innovation capability and its underlying mechanism to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The advantage of this model is that it reflects a larger sample size and more individual dynamic behavior information, which helps to solve the problem of missing variables while ensuring estimation accuracy (Wooldridge, 2008). In addition, the use of the year-industry two-way fixed effect model is to control for unobservable factors at the industry level that change over time (Song et al ., 2022; Aisaiti et al ., 2022). This study constructs the following estimation model:where subscripts i and t represent listed companies and years, respectively; EPIit is the explained variable, that is, the environmental performance index of listed enterprises; digitalit is the explanatory variable, that is, the level of enterprise digitalization; Zit is the relevant control variable that may affect enterprise performance; yearit and industryit are time and industry-fixed effects, respectively; εit is a random error term.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of this model is that it reflects a larger sample size and more individual dynamic behavior information, which helps to solve the problem of missing variables while ensuring estimation accuracy (Wooldridge, 2008). In addition, the use of the year-industry two-way fixed effect model is to control for unobservable factors at the industry level that change over time (Song et al ., 2022; Aisaiti et al ., 2022). This study constructs the following estimation model:where subscripts i and t represent listed companies and years, respectively; EPIit is the explained variable, that is, the environmental performance index of listed enterprises; digitalit is the explanatory variable, that is, the level of enterprise digitalization; Zit is the relevant control variable that may affect enterprise performance; yearit and industryit are time and industry-fixed effects, respectively; εit is a random error term.…”
Section: Methodsmentioning
confidence: 99%
“…Karim et al conducted a qualitative assessment of Bangladesh's renewable energy policy and put forward recommendations, such as strengthening public awareness and increasing investment in renewable energy to promote the renewable energy industry [22]. Additionally, some scholars treated policy implementation as a quasi-natural experiment and analyzed the impact of innovation demonstration zone policies on the level of innovation in cities by using the difference method and found that the establishment of innovation demonstration zones can enhance the level of innovation [23]. Furthermore, it is found that, in recent years, some scholars have adopted the PMC-AE model to conduct quantitative evaluation of manufacturing policies [24].…”
Section: Literature Reviewmentioning
confidence: 99%